Autophagosome-based strategy to monitor apparent tumor-specific CD8 T cells in patients with prostate cancer. (2nd December 2018) - van de Ven, Rieneke; Hilton, Traci L.; Hu, Hong-Ming; Dubay, Christopher J.; Haley, Daniel; Paustian, Christopher; Puri, Sachin; Urba, Walter J.; Curti, Brendan D.; Aung, Sandra; Fox, Bernard A.
ABSTRACT: The immune system plays an essential role in eradicating cancer in concert with various treatment modalities. In the absence of autologous tumor material, no standardized method exists to assess T cell responses against the many antigens that may serve as cancer rejection antigens. Thus, development of methods to screen for therapy-induced anti-tumor responses is a high priority that could help tailor therapy. Here we tested whether a tumor-derived antigen source called DRibbles®, which contain a pool of defective ribosomal products (DRiPs), long-lived and short-lived proteins (SLiPs) and danger-associated molecular patterns (DAMPs), can be used to identify tumor-associated antigen (TAA)-specific responses in patients before or after immunotherapy treatment. Protein content, gene expression and non-synonymous – single nucleotide variants (ns-SNVs) present in UbiLT3 DRibbles were compared with prostate adenocarcinomas and the prostate GVAX vaccine cell lines (PC3/LNCaP). UbiLT3 DRibbles were found to share proteins, as well as match tumor sequences for ns-SNVs with prostate adenocarcinomas and with the cell lines PC3 and LNCaP. UbiLT3 DRibbles were used to monitor anti-tumor responses in patients vaccinated with allogeneic prostate GVAX. UbiLT3-DRibble-reactive CD8 + T-cell responses were detected in post-vaccine PBMC of 6/12 patients (range 0.85–22% of CD8 + cells) after 1 week in vitro stimulation (p = 0.007 vs. pre-vaccine). In conclusion, a cancer-derived autophagosome-enriched preparation, packaging over 100 proteins over-expressed in prostate cancer into microvesicles containing DAMPs, could be used to identify CD8 + T cells in peripheral blood from patients after prostate GVAX vaccination and may represent a general method to monitor anti-cancer T cell responses following immunotherapy.